Strategi Perencanaan Kurikulum Efektif Untuk Peningkatan Mutu Pendidikan - Ratu Safira Aulia; Acep Nurlaeli; Sya'roni Ma'sum (As-Syirkah: Islamic Economic & Financial Journal, 2025)
Curriculum management is a crucial process in the education system, aiming to guide curriculum development and implementation to ensure effectiveness, efficiency, and alignment with students’ needs and contemporary demands. The core functions of curriculum management include planning, organizing, implementing, and supervising, which are integrated to achieve optimal educational goals. The curriculum not only focuses on delivering subject matter but also plays a vital role in shaping students’ character, skills, and competencies, especially in the face of global challenges. Successful curriculum management requires collaboration among educational components, such as school principals, teachers, and policymakers, to ensure implementation aligns with institutional goals. Structured evaluation and continuous supervision are essential to keep the curriculum relevant and responsive to social, technological, and labor market changes. With proper management, curriculum planning can become a strategic instrument for improving the quality of education at various school levels.